Versatile and enhanced tumour modelling in mice via somatic cell transduction. Issue 4 (March 2014) - Rodriguez, Esther; Mannion, Liz; D'Santos, Paula; Griffiths, Meryl; Arends, Mark J; Brindle, Kevin M; Lyons, Scott K
Abstract Genetically engineered mouse (GEM) models of cancer currently comprise the most accurate way to experimentally recapitulate the human disease in the laboratory. Given recent advances in genomics and genetic screens, however, as well as an increasing urgency for the translation of effective preclinical treatments into the clinic, there is a pressing need to make these models easier and more efficient to work with. Accordingly, we have developed a versatile lentivirus‐based approach to induce tumours from somatic cells of GEMs, add or subtract gene expression and render the tumours imageable from a simple breeding stock. The vectors deliver a tamoxifen‐inducible and self‐inactivating Cre recombinase, conditional bioluminescent and fluorescent proteins and an shRNA component. Following the transduction of somatic cells, tumours are initiated by Cre‐mediated recombination of the inherited floxed alleles. Self‐inactivation of Cre expression switches on the expression of luciferase, thereby rendering the recombined cells and resulting tumours bioluminescent. We demonstrate proof of concept of this approach by inducing bioluminescent lung tumours in conditional Kras and p53 mice. We also show that a variant vector expressing shRNA alters tumour growth dynamics and the histological grade associated with the inherited genotype. This approach comprises a versatile means to induce imageable and spontaneous tumour burden in mice. The vectors can be readily customized at the bench to modify reporter readout or tumour phenotype without additional transgenic strain development or breeding. They should also be useful for inducing imageable tumours in organs other than the lung, provided that the inherited conditional genotype is sufficiently penetrant. © 2013 The Authors. The Journal of Pathology published by John Wiley & Sons Ltd on behalf of Pathological Society of Great Britain and Ireland.